1983
DOI: 10.1063/1.94445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal nitridation processes on boron and phosphorus diffusion in 〈100〉 silicon

Abstract: The effect of the silicon thermal nitridation processes, nitridation of SiO2 (oxynitridation), and direct nitridation of the silicon surface on boron and phosphorus diffusion is examined. It is found that oxynitridation results in enhanced diffusion of both impurities while direct nitridation of the silicon surface causes retarded diffusion for both. These phenomena are explained by the mechanisms of silicon self-interstitial injection in the case of oxynitridation and self-interstitial depletion in the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Consistent with stacking fault data, nitridation of SiO~ films thermally grown on Si substrate enhances diffusion of P and B and retards the diffusion of Sb dopant profiles located in the Si substrate underneath the nitroxide film (8,9). These phenomena are similar to those observed during oxidation processes (oxidation-enhanced diffusion or OED) and have been attributed to injection of silicon interstitials into the Si substrate during nitridation September 1985 of oxide (8,9).…”
supporting
confidence: 70%
“…Consistent with stacking fault data, nitridation of SiO~ films thermally grown on Si substrate enhances diffusion of P and B and retards the diffusion of Sb dopant profiles located in the Si substrate underneath the nitroxide film (8,9). These phenomena are similar to those observed during oxidation processes (oxidation-enhanced diffusion or OED) and have been attributed to injection of silicon interstitials into the Si substrate during nitridation September 1985 of oxide (8,9).…”
supporting
confidence: 70%
“…It is of interest to know the outcome of solving these equations, since all of the phenomena outlined in the experimental section above are taken into account, and the relative importance of vacancy and interstitial mechanisms can be changed in this model by the use of concentration-dependent diffusivities for vacancy and interstitial components. -In a limited study, Fahey, Greenfield, and Dutton (1983) In assessing the validity of any proposed models for P difFusion based on profile fitting, it is seldom recognized that many of the data used for profile fitting are simply not suitable for model development by the approaches taken thus far. Specifically, it is most often the case that P concentration profiles resulting from chemical depositions have been the object of model fittings.…”
Section: Experimental Evidencementioning
confidence: 99%
“…It has been observed that oxinitridation has similar effects as those observed for pure oxidation on the diffusion of dopants in silicon, i.e. during silicon oxinitridation processing the P or B diffusivity is enhanced and that for Sb is reduced [14,15]. Oxinitridation also causes the growth of stacking faults OSF [14,16] in a similar way as happens for conventional thermal silicon oxidation.…”
Section: Basic Considerationsmentioning
confidence: 72%